2013
DOI: 10.1007/s00213-013-3319-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex on ethanol consumption and conditioned taste aversion in adolescent and adult rats

Abstract: Rationale Vulnerability to alcoholism is determined by many factors, including the balance of pleasurable vs. aversive alcohol-induced sensations: pleasurable sensations increase drinking, aversive sensations reduce it. Both female sex and adolescent age are associated with fewer use-limiting effects of ethanol and more rapid development of alcohol abuse. Objectives This study assessed voluntary drinking and the aversive effects of alcohol in adolescent and adult male and female rats, to determine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 64 publications
19
69
0
Order By: Relevance
“…After three pairings of the CSa and 1.5 g/kg ethanol, males were consuming 94.1% less CSa than they were at baseline; females were consuming 68.9% less (see Table 1). These results are consistent with those obtained by several other research groups (Caihol and Mormede, 2002;Morales et al, 2014;Schramm-Sapyta et al, 2014;Sherrill et al, 2011a). In fact, a relative sensitivity of males as compared to females with this preparation is generally reported, although the strength of the sex difference varies across studies and is dependent upon a number of factors (see Busse et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After three pairings of the CSa and 1.5 g/kg ethanol, males were consuming 94.1% less CSa than they were at baseline; females were consuming 68.9% less (see Table 1). These results are consistent with those obtained by several other research groups (Caihol and Mormede, 2002;Morales et al, 2014;Schramm-Sapyta et al, 2014;Sherrill et al, 2011a). In fact, a relative sensitivity of males as compared to females with this preparation is generally reported, although the strength of the sex difference varies across studies and is dependent upon a number of factors (see Busse et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…One factor that has received considerable attention is the sex of the subject used in the FAL procedure. Sex differences in FAL have been examined with a variety of compounds such as lithium chloride (LiCl) (Chambers et al, 1981;Dacanay et al, 1984), cocaine (Busse et al, 2005;Jones et al, 2006) and ethanol (Caihol and Mormede, 2002;Morales et al, 2014;Schramm-Sapyta et al, 2014;Sherrill et al, 2011a). The relative sensitivity of males (compared to females) within this preparation is generally reported, although the strength of the sex difference varies across studies and is dependent upon a number of factors (see Busse et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, housing conditions are unlikely responsible for sex differences in alcohol drinking. As shown in Table 1, Sluyter et al (2000); Walker et al (2008); Vetter-O’Hagen et al (2009) and Maldonado-Devincci et al (2010) reported that group-housed females voluntarily drank more alcohol than males, whereas Schramm-Sapyta et al (2014) reported a lack of sex differences in voluntary drinking in single-housed rats. Moreover, Varlinskaya et al (2015) reported that adult males and females drank more alcohol under social circumstances than alone.…”
Section: Discussionmentioning
confidence: 96%
“…For example, adolescent rats consistently display weaker drug-induced CTA compared to adults when conditioned with a number of different compounds such as amphetamine (Infurna & Spear, 1979), cocaine (Schramm-Sapyta et al, 2006), ethanol (SchrammSapyta et al, 2010Vetter-O'Hagen et al, 2009), morphine , and nicotine (Wilmouth and Spear, 2004;Shram et al, 2006), among others (Anderson et al, 2010;Anderson et al, 2014;Flax et al, 2015;Schramm-Sapyta et al, 2007;Wetzel et al, 2014). The relatively weaker taste avoidance reported in adolescents has been suggested to be a function of their relative insensitivity to the drug's aversive effects (Schramm-Sapyta et al, 2014), i.e., the drug is less aversive in adolescent subjects and thus induces a weaker avoidance response.…”
Section: Introductionmentioning
confidence: 99%